Quantitative Analysis of Phytochemicals and Antioxidant Activity in Vitro Ethanol Extract of Jengkol Fruit Peel (Archidendron pauciflorum (Benth.) I.C.Nielsen) - Dinda Hani'ah Arum Saputri; Desak Made Malini; Nining Ratningsih (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Jengkol (Archidendron pauciflorum (Benth.) I.C.Nielsen) is a widely consumed crop in Indonesia, while its fruit peel is generally considered an agricultural waste and underutilized. This study aimed to evaluate the phytochemical content and in vitro antioxidant activity of an ethanol extract of jengkol fruit peel. Phytochemical screening was performed to identify the presence of flavonoids, total polyphenols, and tannins, while antioxidant activity was assessed using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. All experiments were conducted in duplicate, and the results were expressed as mean ± standard deviation. Data were analyzed using descriptive statistical analysis and linear regression to determine IC50 values. Phytochemical analysis showed that the extract contained flavonoids (0.23%), total polyphenols (28.82%), and tannins (3.83%). The ethanol extract of jengkol fruit peel showed very strong in vitro antioxidant activity, with an IC₅₀ value of 6.3 ppm. The high antioxidant activity is likely attributable to the presence of phenolic compounds, which contribute to free radical scavenging by donating electrons or hydrogen atoms. However, this study was limited to in vitro evaluation using a single antioxidant assay method. Further studies employing additional antioxidant assays and in vivo assays are needed to more comprehensively evaluate the potential of jengkol fruit peel extract as an antioxidant.